Banaag at sikat : metakritisismo at antolohiya - Reyes, Maria Luis Torres. 4 0 16; 5 (Manila, Philippines : National Commission for Culture and the Arts, 2010)
Collection of literary criticism of a novel Banaag at Sikat by Lope K. Santos from 1907-1980.
Keywords: 2 -- 0; 6; Philippine fiction (Tagalog).; 20; 2